Impact of Dietary Enrichment with Omega-3 Polyunsaturated Fatty Acids from Extruded Linseed and Padina pavonica Algae Extract on Growth Performance and Metabolic Status in Fattening Rabbits - Alda Quattrone; Doriana Beqiraj; Nour Elhouda Fehri; Rafik Belabbas; Daniele Vigo; Laura Menchetti; Olimpia Barbato; Sebastiana Failla; Massimo Faustini; Shereen Salama Ghoneim; Bayrem Jemmali; Simona Mattioli; et al. (Animals)
This study evaluated the effects of dietary supplementation with omega-3 polyunsaturated fatty acids from extruded linseed, alone and combined with Padina pavonica algae extract, on growth performance and metabolic status in fattening rabbits. Sixty New Zealand White rabbits were assigned to three groups, as follows: control (CNT), L (5% linseed), and LPP (3.5% linseed + 0.2% algae extract) from weaning (37 days) to slaughter (85 days). Productive performance was assessed through body weight (BW), average daily gain (ADG), feed conversion ratio (FCR), and feed intake (FI). Blood was sampled at weaning, 60 days, and slaughter and analyzed for insulin, leptin, cortisol, thyroid hormones (T3, T4), glucose, and non-esterified fatty acids (NEFAs). The L group showed significantly higher ADG (41.0 ± 1 g/d) and improved FCR (4.1 ± 0.2) compared to LPP (ADG: 37 ± 1 g/d, FCR: 4.6 ± 0.2; p = 0.001). No differences were observed in final BW or FI among groups (p < 0.001). Insulin peaked at 60 days across all groups (p < 0.001), with the LPP group showing the lowest levels (9.8 ± 0.9 µUI/mL; p = 0.043). T3 and T4 increased significantly with age (p < 0.001), and the T3/T4 ratio varied by diet and time (p = 0.005). Cortisol rose only at slaughter (p < 0.001) and negatively correlated with insulin and thyroid hormones. The results suggest that omega-3-rich nutraceuticals can enhance growth performance without disrupting metabolic balance and may modulate specific hormonal responses due to their bioactive compounds.